Pembangkitan Listrik Memanfaatkan Arus Lalu Lintas untuk Lampu Lalu Lintas - Yohannes Ridwan Siagian; Adi Asmariadi Budi; Gama Hafiz Aditya; Galih Widayanto (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
Traffic lights has function to regulate the traffic on intersection road, and if electricity off happen so the traffic lights will off too, and traffic jam will happen as the impact of that. Traffic flow can be used as the source of energy by taking the pressure from vehicle which flow on the road. The device to harvest that energy shaped like speed bump and called as Traffic Flow Power Plant (PLTAL). When vehicle flow through that device, it will press the device. Those pressure then will rotate the flywheel which then will rotate generator. The electricity which produce from generator then stored into accumulator which will be used as the electricity source for the traffic lights. Electrical power which produce from a set of PLTAL is 28 Watt, and power needed to light a set of traffic lights is 21,6 Watt. Based on that can be concluded that a set of PLTAL can fulfill electrical power for a set of traffic lights.